INTERNALIZATION OF VEGETARIANISM LIFESTLYE VALUES INTO VEGETARIAN ACTORS - Suryo, Fiona Dewi; Agustiningsih, Glorya (Jurnal Komunikasi dan Bisnis, 2022)
Vegetarian lifestyle begins to grow and becomes a new trend in the society because of their awareness of healthy life that is affected from their food consumed in daily life. Being a vegetarian is an individual choice of life, which she/he has a different way of life and usually lives in families and communities whom unfamiliar with its vegetarian concepts. Therefore, the vegetarians are often considered as “strangers” by people live surround their environment because they have different food habits. This study aims to discuss about internalization process of individuals in adopting life values which affected their decision of becoming vegetarians. The study uses social construction theory as a ground theory, which focusing on the process of internalization among its three other processes. This research uses qualitative method which explores data from in-depth interview. The result is the informants have strong motives, emotions, beliefs, habits, and willingness inside their mind to be vegetarians, whilst the role of the significant others and reference groups do not affect the decision of becoming vegetarians.